Cyclic (ϕ)-Contractions in Uniform Spaces and Related Fixed Point Results - N. Hussain; E. Karapınar; S. Sedghi; N. Shobkolaei; S. Firouzian (Abstract and Applied Analysis)
First, we define cyclic (ϕ)-contractions of different types in a uniform space. Then, we apply these concepts of cyclic (ϕ)-contractions to establish certain fixed and common point theorems on a Hausdorff uniform space. Some more general results are obtained as corollaries. Moreover, some examples are provided to demonstrate the usability of the proved theorems.